Peran Media Informasi pada Perilaku Seksual Remaja - Rosita Passe; Nurul Fitri Sugiarti Syam; Ayu Lestari; Jumrah Sudirman (Jurnal Pengabdian Pada Masyarakat, 2021)
ROLE OF INFORMATION MEDIA ON ADOLESCENT SEXUAL BEHAVIOR. Youth is an important phase of life in an individual’s developmental cycle. This phase is a transition period that can be directed towards the development of a healthy adulthood, thus bringing happiness and success in carrying out developmental tasks in the next phase. The purpose of community service is expected to be a medium for the dissemination of information related to the role of Information media in adolescent sexual behavior. This community service partner is Megarezky University and CV. Faira Aksara with lecture method using zoom application. From the processed data using Wilcoxon test with a sample number of 53 people obtained there was an increase in knowledge from the average value of quisioner pre-test obtained the correct answer value of 63.20 after counseling changed to 77.73. with a value of ρ 0.000. Community Service activities are one of the means of conveying information to teenagers, health workers, teachers, and parents so that it can be applied to teenagers both in the school environment or at home and in the youth social environment.